2005
DOI: 10.1124/mol.105.015586
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of β-Tubulin on Glu 198 by a Microtubule Disrupter

Abstract: We have shown that ␤-tubulin was alkylated by a microtubule disrupter, urea (ICEU), on a glutamic acid residue at position 198 and not on the previously proposed reactive cysteine 239. ICEU belongs to the 4-substituted-phenyl-NЈ-(2-chloroethyl) urea class that alkylates mainly cellular proteins. Previous studies have shown that the tertbutyl (tBCEU) and iodo (ICEU) derivatives induce microtubule disruption because of ␤-tubulin alkylation. tBCEU was supposed to bind covalently to cysteine 239 of ␤-tubulin, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…The demonstration that the alkylation of Cys239 by tBCEU was indirect and based on the previous work by other groups (Ludueñ a and Roach, 1981b). However, by using MALDI-TOF mass spectrometry and 1-(2-chloroethyl)-3-(4-iodophenyl)urea (ICEU), a bioisostere of tB-CEU (Bouchon et al, 2005), we were unable to confirm this proposed mechanism of action. The mass spectrometric analysis completely excluded thioalkylation of Cys239 by ICEU as initially proposed but instead uncovered the unique and rather unexpected covalent binding of the drug onto Glu198 through the formation of an ester bond.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The demonstration that the alkylation of Cys239 by tBCEU was indirect and based on the previous work by other groups (Ludueñ a and Roach, 1981b). However, by using MALDI-TOF mass spectrometry and 1-(2-chloroethyl)-3-(4-iodophenyl)urea (ICEU), a bioisostere of tB-CEU (Bouchon et al, 2005), we were unable to confirm this proposed mechanism of action. The mass spectrometric analysis completely excluded thioalkylation of Cys239 by ICEU as initially proposed but instead uncovered the unique and rather unexpected covalent binding of the drug onto Glu198 through the formation of an ester bond.…”
Section: Introductionmentioning
confidence: 66%
“…For nano-ESI MS/MS, cells were treated with a 100 M concentration of the drugs for 16 h. For EBI analysis, cells were incubated with a 100 M concentration of the reagent for 2 h (Legault et al, 2000). Protein extracts for twodimensional electrophoresis were prepared essentially as described by Bouchon et al (2005). In brief, after incubation with the drugs at the indicated concentration and time, cells were harvested by scraping, pelleted by centrifugation, and washed twice with phosphatebuffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…This makes more possible that the difference in the gel mobility is dependent on (c). According to previous reports (29,30), the involved posttranslational change could be an alkylation, which is, to our knowledge, the only change that produces a difference in the net charge of the protein capable to underlie a basic shift in the pI of this order and the concomitant faster migration during gel electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, ICEU exhibits a calculated Log P of 2.8 (ChemDraw software) and has been shown to interact easily with model lipid bilayer membranes (Saint-Laurent et al, 2001). Considering the cytotoxic activity of ICEU, it was recently demonstrated on B16 melanoma cells that the mechanism of action of ICEU was mediated through its covalent binding to a glutamic acid residue at position 198 of b-tubulin isoform 5 (Bouchon et al, 2005). In CT-26 cells, ICEU induced similar modifications of the b-tubulin migration properties on SDS -PAGE.…”
Section: Discussionmentioning
confidence: 99%
“…N-(4-iodophenyl)-N 0 -(2-chloroethyl)-urea (ICEU) was selected for study on the basis of a low inhibition concentration (IC 50 ) on several tumour cell lines resistant to numerous other chemotherapeutic agents. In vitro studies have shown that ICEU cytotoxicity is linked to cytoskeleton disruption following microtubule depolymerisation, resulting from b-tubulin alkylation of the glutamic acid residue at position 198 (Petitclerc et al, 2004;Bouchon et al, 2005). Finally, ICEU has displayed significant antitumoral activity in the murine CT-26 colon carcinoma model, antitumoral activity that is, at least partly, associated with an antiangiogenic effect Petitclerc et al, 2004).…”
mentioning
confidence: 99%